An Analysis of The Romanian High Education System Perspectives using Quantitative Techniques. (13th May 2015) - Cristache, Silvia-Elena; Serban, Daniela; Vuta, Mariana
Abstract: Participation rate to education for Romanian population between 15 and 24 years old is situating Romania on the last places compared to the other European countries. The paper aim is to establish the main influence factors over the measures charactering the high education system evolution in Romania during the world economic crisis. There are differences concerning the participation rate to education by gender, the feminine population having a bigger rate, and there are also differences between the urban and the rural areas. The main methods used in the paper are discussion the correlation and multiple regression models between the scholar population, education human resources, number of graduates of high education, the rate of participation to high education and the share of GDP allocated. Analysis and modeling (correlation analysis, multiple regression models, associations analysis) are realized using E-views and Excel programs. The increasing tendency of the participation rate to education can be explained mainly by the increase of the participation rate to high education. If Romania is still behind other European countries in spied of the increasing tendency of the cost per student and of connected to the high education graduates.